PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Muhammad Fahri Rizqi; Ani Rosidah; Ari Yanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the Discovery Learning model in social studies learning in fifth grade elementary school to improve students' critical thinking skills. The research approach used is descriptive qualitative with a sample of one class consisting of 13 students, using data collection techniques in the form of observation, interviews, and documentation of student worksheets. The results show that the application of Discovery Learning increases student activity in exploring, discussing, and analyzing the causes and effects of social and cultural phenomena. Students are able to formulate critical questions, connect concepts with everyday experiences, and make simple inferences and recommendations. The stages of identification, exploration, data processing, and reflection systematically encourage metacognition and self-evaluation, which are indicators of advanced critical thinking. The obstacles found include time constraints, teacher readiness, and learning tools, which require adjustments in classroom management and school support. Overall, this study confirms that the application of the Discovery Learning model is effective in improving critical thinking skills in social studies learning in elementary schools, while also providing practical contributions for teachers in designing more constructive, reflective, and discovery-oriented learning. These findings are expected to form the basis for the development of learning strategies that further foster critical thinking skills.